2021
DOI: 10.3390/molecules26061782
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan Films Obtained from Brachystola magna (Girard) and Its Evaluation on Quality Attributes in Sausages during Storage

Abstract: High molecular weight chitosan (≈322 kDa) was obtained from chitin isolated from Brachystola magna (Girard) to produced biodegradable films. Their physicochemical, mechanical and water vapor permeability (WVP) properties were compared against commercial chitosan films with different molecular weights. Brachystola magna chitosan films (CFBM) exhibited similar physicochemical and mechanical characteristics to those of commercial chitosans. The CFBM films presented lower WVP values (10.01 × 10−11 g/m s Pa) than c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 65 publications
(99 reference statements)
0
2
0
Order By: Relevance
“…The first study, chitosan films from mealworms (Tenebrio molitor) (812 kDa) and grasshoppers (Brachystola magna) (696 kDa) were found to have statistically similar TS and E%, when compared to the study's low (759 kDa) and medium (870 kDa) molecular weight reference chitosan films [31]. In another study, grasshopper (B. magna) chitosan (322 kDa) films were compared to high, medium, and low molecular weight crustacean chitosan films [41]. They showed that grasshopper films had significantly lower TS values than high and medium molecular weight commercial chitosan, but films were statistically similar to low molecular weight crustacean chitosan.…”
Section: Mechanical Propertiesmentioning
confidence: 92%
See 1 more Smart Citation
“…The first study, chitosan films from mealworms (Tenebrio molitor) (812 kDa) and grasshoppers (Brachystola magna) (696 kDa) were found to have statistically similar TS and E%, when compared to the study's low (759 kDa) and medium (870 kDa) molecular weight reference chitosan films [31]. In another study, grasshopper (B. magna) chitosan (322 kDa) films were compared to high, medium, and low molecular weight crustacean chitosan films [41]. They showed that grasshopper films had significantly lower TS values than high and medium molecular weight commercial chitosan, but films were statistically similar to low molecular weight crustacean chitosan.…”
Section: Mechanical Propertiesmentioning
confidence: 92%
“…Little research is available on the water vapor permeability on insect chitosan films, making it difficult to understand the molecular differences responsible for the decreased film WVP. In one study, the WVP of glycerol-chitosan films from grasshoppers was evaluated and compared to low, medium, and high molecular weight commercial chitosan [41]. The authors reported grasshopper chitosan films had the lowest WVP (1 × 10 −10 g/m•s•Pa) compared to all shrimp chitosan films (1.6 to 6.43 × 10 −10 g/m•s•Pa).…”
Section: Water Vapor Permeability (Wvp)mentioning
confidence: 99%